Drivers of preventive care (under)delivery for cardiovascular diseases: evidence from a randomized study with standardized patients in India - Pillai, Vasanthi Subramonia; Favaretti, Caterina; Jose, Sandra; Jose, Jithin; Ali, Mohammed K.; Mcconnell, Margaret; Sudharsanan, Nikkil (American Journal of Health Economics, 2026)
Abstract Clinicians in low- and middle-income countries often deviate from care guidelines and underdeliver high-value preventive care. Focusing on hypertension screening, we investigate several explanations for underdelivery using a randomized experiment with standardized patients (SPs). Across 600 clinics in two major Indian cities, we found that nearly half of clinicians failed to screen SPs—even though screening is highly cost-effective and universally recommended by Indian guidelines. We did not find evidence that underscreening was driven by an absence of equipment and staff or a lack of clinicians’ knowledge on how to screen for hypertension. Our results also suggest that screening is not driven by time pressure nor by clinicians' personal judgment on which patients should be screened. However, we find notable differences between public and private facilities, with clinicians in private facilities screening significantly more often. Overall, we find that conventional explanations for underdelivery—such as screening knowledge, resources, or time pressure—may not be the prime drivers of inadequate preventive care provision in the Indian setting. Rather, our results suggest that clinician effort in India is highly influenced by provider care environments and incentive structures.
Online veröffentlicht: 17. Dezember 2025
Gesehen am 12.02.2026